Meningkatkan Motorik Kasar Anak Usia 5-6 Tahun Melalui Kegiatan Bermain Petak Umpet di TK Bhakti Pertiwi - Dwi Fungsiari; Melvi Lesmana Alim; Rizki Amalia (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low gross motor skills of children aged 5-6 years at TK Bhakti Pertiwi, Kampar Regency. For this reason, a concrete application is needed to be able to find the right way to deal with children's gross motor skills, namely playing hide and seek. This research aims to find out whether playing hide and seek can improve gross motor skills in children aged 5-6 years at TK Bhakti Pertiwi, Kampar Regency. This type of research is classroom action research which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together with a total of 13 children. Data collection techniques for data collection in this research are observation and documentation. The data analysis technique used in this research is the percentage technique. From the results of classroom action research and discussions as described, a conclusion was drawn regarding the results of this research, namely that the application of playing hide and seek can improve the gross motor skills of children aged 5-6 years at TK Bhakti Pertiwi, Kampar Regency. The gross motor skills of children aged 5-6 at TK Bhakti Pertiwi, Kampar Regency through playing hide and seek have increased every cycle. In the pre-cycle, an average score of 38.85% was obtained with the BB (Not Yet Developed) criteria. After improvements were made in cycle I, a score of 54.04% was obtained with MB (Starting to Develop) and in cycle II a score of 80.19% was obtained with BSB (Very Well Developing) criteria. Keywords: Playing Hide and Seek, Gross Motor Skills Children, Aged 5-6 Years.